ANALYSIS OF FINANCIAL PERFORMANCE OF THE REGIONAL GOVERNMENT OF PARIGI MOUTONG DISTRICT - Wahyu, Wahyu; Afriza, Afriza; Muslimin, Muslimin; Husnah, Husnah (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2022)
This research aims to analyze the financial performance of the local government of Parigi Moutong District in the period 2016-2021 by using the ratio analysis method of PAD growth, decentralization, independence, PAD effectiveness, expenditure growth, expenditure compatibility consisting of operational and capital expenditures, and expenditure efficiency by using a quantitative descriptive approach. The results of the research show that (1) The PAD growth analysis has a positive category with an average percentage value of 11.73%, and (2) The ratio analysis of the degree of decentralization has a very low category with a percentage value of 9.07%, (3) Ratio analysis of regional financial independence has an instructive category with a percentage value of 13.14%, (4) PAD effectiveness ratio analysis has a very effective category with a percentage value of 105.40%, (5) Growth Analysis expenditure has a positive category with a percentage value of 4.76%, (6) The analysis of the compatibility ratio consisting of operational and capital expenditure has a balanced category with a percentage value of 64.13% and 16.20%. (7) The expenditure efficiency ratio analysis has an efficient category with a percentage value of 94.53. Keywords: PAD Growth, Degree of Decentralization, Independence, PAD Effectiveness, Expenditure Growth, Harmony, Expenditure Efficiency.